Some Exact Bianchi Types Cosmological Models in f(R, T) Theory of Gravity - Ahmed Al-haysah; Abdulvahid Hasmani (Journal of Mathematical Sciences and Modelling, 2019)
In this paper, we attempt to study spatially homogeneous Bianchi types-III, V, VI$_0$ $&$ VI$_h$ cosmological models in $f(R, T)$ theory of gravity. Here the models are obtained by assuming forms of the function $f(R, T)$ as $f(R, T)= R + 2f(T)$ and $f(R, T) = f_1(R)+f_2(T)$. The exact solutions of Einstein's field equations (EFEs) have been obtained for two different types of physically viable cosmologies using a special form of Hubble parameter (HP). The physical and geometrical properties of these models have been discussed and expressions for the Ricci scalar $R$ in each case are obtained.